1991
DOI: 10.1007/bf03341303
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Assaults Against Psychiatric Residents

Abstract: There are few studies of assaults against psychiatric residents. The only two domestic studies specifically investigating assaults against residents each surveyed a single residency program. In the present study, 333 psychiatric residents in 11 training programs in Pennsylvania were surveyed about assaults and threats on them during residency. One hundred fifty-five questionnaires (46%) were completed and returned. Of the respondents, 41 % experienced a physical assault and 48% were threatened at some time dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 7 publications
3
28
1
Order By: Relevance
“…The highest risk seems to be in psychiatry physicians in training, clinical psychologists, and residents of other specialties in a psychiatric rotation. 12,13,32,33 Main causes for psychiatric aggressiveness are overcrowded wards, unsuitable conditions for patients, poor interpersonal skills, 34 poor training, less experience with the management of aggressive patients, 35 and certain psychiatric disorders, such as acute schizophrenia, alcohol and substance abuse, and bipolar disorder. The physicians in training are more exposed to this phenomenon due to: a defective training in violence management, 36 inadequacies regarding the identification of violent and pre-violent acts and behaviors, 35 difficulties in directing their attention to the anxiety and fears aroused when dealing with a violent patient, 37 difficulties in identifying the needs of patients with violent behaviors, the misconception that residens must "suck it up" (abuse and harassment is considered part of the job), 4 difficulties in reporting harassment/abuse, or not knowing where to go to report it, 4 fear of reprisal, 4 misconception that nothing can be done to minimize this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The highest risk seems to be in psychiatry physicians in training, clinical psychologists, and residents of other specialties in a psychiatric rotation. 12,13,32,33 Main causes for psychiatric aggressiveness are overcrowded wards, unsuitable conditions for patients, poor interpersonal skills, 34 poor training, less experience with the management of aggressive patients, 35 and certain psychiatric disorders, such as acute schizophrenia, alcohol and substance abuse, and bipolar disorder. The physicians in training are more exposed to this phenomenon due to: a defective training in violence management, 36 inadequacies regarding the identification of violent and pre-violent acts and behaviors, 35 difficulties in directing their attention to the anxiety and fears aroused when dealing with a violent patient, 37 difficulties in identifying the needs of patients with violent behaviors, the misconception that residens must "suck it up" (abuse and harassment is considered part of the job), 4 difficulties in reporting harassment/abuse, or not knowing where to go to report it, 4 fear of reprisal, 4 misconception that nothing can be done to minimize this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Yet , th e rel ation ship was not stat ist ica lly significant. In other studies, ag e and number of attacks ha ve not been cor re la t ed (2,4). Resea rch by Madden, Lion, a nd Penna (1976) suggests that level of expe rience (yea r in trainin g) may be associated with assault .…”
Section: (Sugges Te D Abstract Index M Cdi Cus M Esh: Assault T Hrementioning
confidence: 89%
“…Fink, Shoe 1', a nd Burin ( 1991) rep orted that 41% had been assa ulted a nd 48 % had been threa te ned of 333 psychi atric resid ents surveyed in Pennsylvan ia (4). More rece ntl y, Black e t a l. (1994) found t hat a sign ifica n t propor tion (56 %) of residents in a n East ern psychi a t ry pro gram had been assau lt ed , with nearly a ll resid ents receivin g ve rba l threat s (5) .…”
Section: (Sugges Te D Abstract Index M Cdi Cus M Esh: Assault T Hrementioning
confidence: 99%
“…10 Similarly, studies from North America consistently report that 40% of psychiatric trainees have experienced a physical assault at work. [11][12][13][14] Violence with weapons and verbal assault Although reports of assault with weapons are infrequent, one US study reported psychiatric trainees frequently discovering weapons on patients in the emergency room. 11 Conversely, verbal assault of trainee psychiatrists is widely reported -just over 70% of trainees had been threatened by a patient.…”
Section: International Studiesmentioning
confidence: 99%